Dampak Manajemen Sumber Daya Manusia dan Pengelolaan Keuangan Terhadap Penjaminan Mutu Pendidikan dengan Pengelolaan Kelas Sebagai Variabel Mediasi di Sekolah Dasar Negeri Sepang Kecamatan Serang - Fitria Handayani; Andriani Sariwardani; Mutoharoh Mutoharoh (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Primary education plays a crucial role in shaping students' character and abilities as a foundation for further development at higher levels of education. Therefore, it is essential to ensure the maintenance of education quality through various influencing factors, one of which is human resource management (HRM) and financial management. The purpose of this study is to analyze the impact of HRM and financial management on the assurance of education quality at Sepang State Elementary School in Serang District, with classroom management as a mediating variable. This research uses a quantitative approach that combines descriptive and causal designs to examine the relationships between the variables under study. The research sample consists of the school principal, teachers, and administrative staff at Sepang State Elementary School in Serang District. Data collection was carried out through the distribution of questionnaires to the respondents, and the collected data were analyzed using descriptive statistics and path analysis. The results indicate that optimal human resource management has a significant positive impact on improving the quality assurance of education, mediated by effective classroom management. Furthermore, good and well-planned financial management also plays a crucial role in supporting the improvement of education quality. Classroom management, as a mediating variable, strengthens the relationship between HRM, financial management, and education quality assurance. These findings emphasize that the quality of education greatly depends on the integration of internal school factors, including human resource management, financial management, and the quality of classroom management. This study provides practical contributions for schools and the government in formulating policies to improve education quality through good human resource management, transparent financial management, and the implementation of efficient and effective classroom management. Theoretically, this research also offers new insights into the development of educational management models at the elementary school level, particularly in Indonesia.